Dettagli per l'involucro del terminal verde / Envelope's Details for the Green Airport Terminal - Esposito, Maria Antonietta (Firenze University Press, 2010)
Envelope's Details for the Green Airport Terminal is a contribution to airport design at working plan level, although its contents may be generalized and applied to the definition of performances as well as to the design solutions for the building's envelope itself. The airport is considered a critical and complex system in the matter of sustainability. The vision of life-cycle typical of air terminal design processes may be transferred to the technical choices pertaining its envelope. The volume discusses these issues in a practical and user oriented way, analyzing Performance Based Design documentation; Performance sheets samples; Bid documentation; Building Technology items; Bill of Quantities rules and samples; Technical Solutions by international drawing standards. Details catalogue and updated references lists are included